Histological and Histochemical Studies on Small Intestine of Sheep (Ovis aries) and Goat (Capra hircus) - Gutte, M.M. (Indian Journal of Veterinary Anatomy, 2019)
The wall of small intestine was made up of basic four histological tissue layers viz; tunica mucosa, submucosa, muscularis and serosa. The mucosa was lined by the simple columnar epithelium with goblet cells. The crypts of lieberkuhan was present throughout mucosa of all segments of small intestine in both the species. The Brunner’s glands were more prominent in duodenum of both the species. The shape of the villi was different in various segments of small intestine. The tunica muscularis was consisted of inner circular and outer longitudinal layers of smooth muscle fibres. The height and width of villi was more in goat than sheep. The height and width of crypts of Lieberkuhn has non-significant difference in all segments of both the species. The reaction for the glycogen and neutral mucopolysaccharides was observed intense to moderate in various components of small intestine of both the species.